Monitoramento de estratégias de nucleação para restauração ecológica no bioma Mata Atlântica, sul do Brasil - Silva, Marcela Peuckert Kamphorst Leal da (2017)
The Atlantic Forest biome is considered one of the most important regions for biodiversity conservation in the world due to the combination of high species richness and a high number of endemic species. Ecological restoration strategies based on the principles of nucleation assist in the return of functions and ecological processes of disturbed areas, in order to facilitate and accelerate the process of ecological succession, respecting their natural diversity. The present work aims to analyze the efficiency of different nucleating strategies for the ecological restoration of forest ecosystems in the Atlantic Forest biome of Rio Grande do Sul, Brazil. The study was developed in riparian forests around springs, with predominance of eucalyptus productive matrix, in Itaara, RS. For this, were planted 300 seedlings of ten species arranged in 60 nuclei. Ten artificial perches were also installed with seed collectors and 10 witness collectors, in addition to the monitoring of the avifauna. Total height, DAS, survival rates and reproductive phenology (flowering and fruiting) were evaluated. Survival rates showed significant differences. Allophylus edulis, Campomanesia xanthocarpa, Eugenia involucrata, Luehea divaricata, Parapiptadenia rigida, Prunus myrtifolia, Psidium cattleianum and Schinus terebinthifolius showed 100% survival. Cupania vernalis was the only one to present a critical rate of 45%. Increases in height and in DAS also showed significant differences, with most of the pioneer species presenting the highest averages for both variables. Schinus terebinthifolius and Psidium cattleianum showed flowering and fruiting 12 months after planting. Pioneer species were the most efficient in survival and growth than species of more advanced successional stage. Schinus terebinthifolius was the best performing species for the evaluated variables. A total of 4,089 seeds belonging to 12 species were sampled on collectors. Of this total, 2,110 (51.60%) seeds were sampled in the collectors under artificial perches and 1,979 (48.40%) sampled in the control collectors. There was no significant difference between the treatments by the Kruskal-Wallis test at a 5% probability level for the seeds number. Tyrannus melancholicus was the only species to use the perches. The use of artificial perches was not efficient for the supply of plant propagules nor for the attraction of birds. It was concluded that the arrangement in nuclei allowed the satisfactory development of most species, and that the productive matrix of eucalyptus surrounding the area negatively influenced the processes of seed dispersal.